Religion: A Belief in Context with Hindutva: Understanding Hindutva: A Historical, Ideological, and Constitutional Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The word religion originally originates from the Latin word ‘religio’ whose meaning is bond and obligations. On a global historical scene, a precise and definite period of religion has not been told nor has it been found that the who use the word ‘Dharma’ very first time. Due to ideological differences, according to many thinkers the use of word religion came in force in 16 or 17 Century, after the arrival of the Bible. But if seen theoretically, 50000 years BC religious beliefs have been confirmed. As time changed, religious ideas acquired their important place in human life. On the global level, if we talk about religion, America, Britain, Europe, Asia, Latin America, South Africa and Indian subcontinent are found to have many types of religion, and their history is equal to the history of human life. Gradually religious ideas contributed to change in human life. According to the topic the main motive of this research is to elaborate ‘Hindutva’ in India. Indian constitution provides security to every citizen of India about religion. All religions have equal protection in the Indian system, which has been made in the preamble of the Indian Constitution that India will be a secular state. Secularism means that all religions have equal respect in India. No discrimination will be made with people of any religion and the state will not preserve any religion i.e. no particular religion will be encouraged by the state. Many historians describe that India was a Hindu country but after the colonial war in the world many religion came in existence and they are growing in good atmosphere in India. India is the only country in the world where followers of different religions are living together with love and they pay respect to all religions equally. The conspirators have been working from time to time to launch poison in the atmosphere of this country. But with the understanding of the Indian public, everything is ending itself.